1999
DOI: 10.4269/ajtmh.1999.60.263
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of risk factors for Haemophilus influenzae type B disease in Navajo children.

Abstract: Abstract. To understand the potential risk factors and protective factors for invasive Haemophilus influenzae type b (Hib) disease, we conducted a case-control study among Navajo children less than two years of age resident on the Navajo Nation. We analyzed household interview data for 60 cases that occurred between August 1988 and February 1991, and for 116 controls matched by age, gender, and geographic location. The Hib vaccine recipients were excluded from the analyses. Conditional logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The 12 case-control studies on SHS exposure and invasive Hib disease included a total of 1,228 cases and 3,076 controls (Table 1) [3],[36],[44][53]. The overall effect size was positive but nonsignificant (pooled OR 1.22, 95% CI 0.93–1.62; test of heterogeneity p =  0.011, I 2  = 55.0%) (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 case-control studies on SHS exposure and invasive Hib disease included a total of 1,228 cases and 3,076 controls (Table 1) [3],[36],[44][53]. The overall effect size was positive but nonsignificant (pooled OR 1.22, 95% CI 0.93–1.62; test of heterogeneity p =  0.011, I 2  = 55.0%) (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…In subgroup analysis, studies with laboratory-confirmed diagnosis had a similar effect size of 1.24 (95% CI 0.86–1.78), whereas adjusted studies yielded a lower and nonsignificant effect size (OR 1.10, 95% CI 0.80–1.51) [3],[36],[44],[46][53]. Studies on preschool children had a significant positive association (OR 1.46, 95% CI 1.19–1.81) (Table 2) [3],[36],[44][47],[49],[52],[53]. Studies before 1990, when Hib vaccine was not yet commonly available, had a stronger positive association (OR 1.49, 95% CI 1.16–1.93) than the overall analysis [3],[44][47].…”
Section: Resultsmentioning
confidence: 99%
“…In the Arctic, an augmented transmission rate of H. influenzae was reported to be associated with smoking in pregnancy, prematurity, lack of breastfeeding, shared care with more than one child younger than 2 years of age, adoption status, Inuit ethnicity, as well as with wood heating, rodents in the home, livestock near the home, overcrowding and rural residence (Banerji et al , 2009; Hennessy et al , 2008). In Navajo children, poor housing conditions, such as a lack of an in-home water service, were reported to increase H. influenzae type b infection rates (Wolff et al , 1999). Similar socio-economic factors underlying an increased susceptibility to invasive H. influenzae disease are commonly present in various indigenous populations (Tsang et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among young children, greater exposure to the pathogen due to poor housing conditions, such as overcrowding and lack of access to adequate volume of water in the home may cause high transmission rates of H. influenzae [71]. Several epidemiological studies have found an association of invasive Hib disease with indicators of low socioeconomic status (low income, single parents, low parental education levels, household crowding, indoor wood heating, rodents in the home), number of children in a family, shared childcare facilities, parental smoking and lack of breastfeeding in Navajo and Alaska Native children [22, 72]. High burden of chronic conditions, such as obesity, diabetes, chronic obstructive pulmonary disease, tuberculosis as well as a prevalence of smoking, alcohol and substance abuse that have been identified as important health issues in Canadian Indigenous populations [73] may have a negative effect on natural immunity against H. influenzae in the population and hence contribute to an enhanced circulation of the pathogen in Indigenous communities.…”
Section: The Role Of Socioeconomic Risk Factors In Susceptibility To Invasive H Influenzae Diseasementioning
confidence: 99%